Bioethanol production from tacca leontopethaloides starch by co-culturing of ragi tapai with saccharomyces cerevisiae in a stirred bioreactor tank: article - Nagor Ghani, Mohammad Nabil; Sauid, Suhaila; Mohd Rodhi, Miradatul Najwa (2019)
Bioethanol can be produced from fermentation of Tacca leontopethaloides starch by culturing or co-culturing Saccharomyces cerevisiae and ragi tapai in bioreator. The comparison study between different cultures for fermentation was done which were single culture of S.cerevisiae, and co-culturing of S.cerevisiae and Ragi tapai. The results show that for single culture, the production of ethanol was averages at 0.2774 g/l which is lower than co-culture which is averages at 0.2805 due to co-culture has better condition to produce more ethanol effectively. The fermentation had been done for 72 hours and the sample was taken every 2 hours for 12 hours and every 6 hours for 60 hours. The total 16 samples was collected throughout the experiment. Glucose content, ethanol and cell dry weight analysis were used in this experiment to observe the production of ethanol.